Platelet Lysate Activates Human Subcutaneous Adipose Tissue Cells by Promoting Cell Proliferation and Their Paracrine Activity Toward Epidermal Keratinocytes - Romaldini, Alessio; Mastrogiacomo, Maddalena; Cancedda, Ranieri; Descalzi, Fiorella (Frontiers in Bioengineering and Biotechnology, 2018)
Skin chronic wounds are non-healing ulcerative defects, which arise in association with a morbidity state, such as diabetes and vascular insufficiency or as the consequence of systemic factors including advanced age. Platelet Rich Plasma, a platelet-rich blood fraction, can significantly improve the healing of human skin chronic ulcers. Given that the subcutaneous adipose tissue is located beneath the skin and plays a role in the skin homeostasis, in this study, we investigated the in vitro response of human subcutaneous adipose tissue cells to platelet content in a model mimicking in vitro the in situ milieu of a deep skin injury. Considering that, at the wound site, plasma turn to serum, platelets are activated and inflammation occurs, human adipose-derived stromal cells (hASC) were cultured with Human Serum (HS) supplemented or not with Platelet Lysate (PL) and/or IL-1α. We observed that HS sustained hASC proliferation more efficiently than FBS and induced a spontaneous adipogenic differentiation in the cells. PL added to HS enhanced hASC proliferation, regardless the presence of IL-1α. In the presence of PL, hASC progressively lessened the adipogenic phenotype, possibly because the proliferation of less committed cells was induced. However, these cells resumed adipogenesis in permissive conditions. Accordingly, PL induced in quiescent cells activation of the proliferation-related pathways ERK, Akt, and STAT-3 and expression of Cyclin D1. Moreover, PL induced an early and transient increase of the pro-inflammatory response triggered by IL-1α, by inducing COX-2 expression and secretion of a large amount of PGE2, IL-6, and IL-8. Media conditioned by PL-stimulated hASC exerted a chemotactic activity on human keratinocytes and favored the healing of an in vitro scratch wound. In order to bridge the gap between in vitro results and possible in vivo events, the stimuli were also tested in ex vivo cultures of in toto human adipose tissue biopsies (hAT). PL induced cell proliferation in hAT and outgrowth of committed progenitor cells able to differentiate in permissive conditions. In conclusion, we report that the adipose tissue responds to the wound microenvironment by activating the proliferation of adipose tissue progenitor cells and promoting the release of factors favoring wound healing.